Consumptıon Rıtual In Javanese Weddıng Ceremony: Ethnography Research In Kabupaten Ngawı - Fatchur Rohman; Taufiq Ismail (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
Consumption ritual gains more attention in consumer behavior study since the trend of ethnic market is ascending for its theoretical enrichment in this topic as well as for its business opportunity. Using ethnography approach, this research aims to reveal the consumption ritual in Javanese wedding ceremony in Kabupaten Ngawi. It explores the common season of Javanese wedding ritual, the sequence of the Javanese wedding ritual, what the consumers have in mind, and what the things needed to arrange such Javanese wedding ritual. In conclusion, Javanese people indeed have seasonal marriage time based on their unique calendar system; besides, it also have diverse sequence from one to another region. Yet, the needs to arrange Javanese wedding ritual are almost similar among regions. Furthermore, the consumer’s perspective in Javanese wedding ritual ends on some interpretations about the meaning of this ritual for them. Besides the theoretical enrichment in consumer behavior, this ritual involves huge resources that will be a market opportunity that the business practitioners may take this advantage.